Correlation of Artemin and GFRα3 With Osteoarthritis Pain: Early Evidence From Naturally Occurring Osteoarthritis-Associated Chronic Pain in Dogs - Minnema, Laura; Wheeler, Joshua; Enomoto, Masataka; Pitake, Saumitra; Mishra, Santosh K.; Lascelles, B. Duncan X. (Frontiers in Neuroscience, 2020)
Arthritis, including osteoarthritis (OA) and other musculoskeletal-associated pain, is a worldwide problem; however, effective drug options are limited. Several receptors, neurotransmitters, and endogenous mediators have been identified in rodent models, but the relevance of these molecules in disease-associated pain is not always clear. Artemin, a neurotrophic factor, and its receptor, glial-derived neurotrophic factor (GDNF) family receptor alpha-3 (GFRα3), have been identified to involved in pain in rodents. Their role in OA-associated pain is unknown. To explore a possible association, we analyzed tissue from naturally occurring OA in dogs to characterize the correlation to chronic pain. We used behavioral assessment, objective measures of limb use, and cellular and molecular tools to identify whether artemin and GFRα3 might be associated with OA pain. Our results using banked tissue from well-phenotyped dogs indicates that artemin/GFRα3 may play an important, and hitherto unrecognized, role in chronic OA-associated pain. Elevated serum levels of artemin from osteoarthritic humans compared to healthy individuals suggest translational relevance. Our data provide compelling evidence that the artemin/GFRα3 signaling pathway may be important in OA pain in both non-humans and humans and may ultimately lead to novel therapeutics.